Analytic Continuation with Pade Decomposition - 韩兴杰 廖海军 谢海东 黄瑞珍 孟子杨 向涛 (Chinese physics letters, 2017)
The ill-posed analytic continuation problem for Green＇s functions or self-energies can be carried out using the Pade rational polynomial approximation. However, to extract accurate results from this approximation, high precision input data of the Matsubara Green function are needed. The calculation of the Matsubara Green function generally involves a Matsubara frequency summation, which cannot be evaluated analytically. Numerical summation is requisite but it converges slowly with the increase of the Matsubara frequency. Here we show that this slow convergence problem can be significantly improved by utilizing the Pade decomposition approach to replace the Matsubara frequency summation by a Pade frequency summation, and high precision input data can be obtained to successfully perform the Pade analytic continuation.